2015
DOI: 10.1021/ac504141j
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric Constant of Liquids Confined in the Extended Nanospace Measured by a Streaming Potential Method

Abstract: Understanding liquid structure and the electrical properties of liquids confined in extended nanospaces (10-1000 nm) is important for nanofluidics and nanochemistry. To understand these liquid properties requires determination of the dielectric constant of liquids confined in extended nanospaces. A novel dielectric constant measurement method has thus been developed for extended nanospaces using a streaming potential method. We focused on the nonsteady-state streaming potential in extended nanospaces and succe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 39 publications
4
35
1
Order By: Relevance
“…The results of the mechanical and electrical tests reported in this work provide clear evidence that the ions in the layered nanostructures are trapped in a more regular structure compared to the liquid phase. A similar effect was experienced by Morikawa et al85 by measuring dielectric constant of water confined in an extended nanospace (10-1000 nm), and showing a significantly reduced value approximately 3 times lower than that for the bulk.The surface-induced formation of thin solid-like insulating IL nanostructures may have a strong impact on the behavior of nanotechnological systems and devices, in particular because such…”
supporting
confidence: 81%
“…The results of the mechanical and electrical tests reported in this work provide clear evidence that the ions in the layered nanostructures are trapped in a more regular structure compared to the liquid phase. A similar effect was experienced by Morikawa et al85 by measuring dielectric constant of water confined in an extended nanospace (10-1000 nm), and showing a significantly reduced value approximately 3 times lower than that for the bulk.The surface-induced formation of thin solid-like insulating IL nanostructures may have a strong impact on the behavior of nanotechnological systems and devices, in particular because such…”
supporting
confidence: 81%
“…The figure shows that this ramping of ε with the default parameters is too fast; we find that ε reaches the bulk limit within 3−4 Å of the surface, which is well within the first water bilayer. This rate of ramping is faster than the experimental 95 and theoretical investigations. 89,96 We also note that here, as illustrated by Figure 1, the ionic charge is unphysically close to the metal slab and a significant proportion lies in the region of vacuum permittivity.…”
Section: Acs Catalysismentioning
confidence: 79%
“…Such confined water was found to show unique properties differing from bulk water, e.g., higher viscosity, lower dielectric constant, enhancement of liquid conductivity, slower translational molecular motion, and higher protonic mobility compared with bulk water. [30][31][32][33][34][35] These results have suggested that local adsorbed water layers on surfaces and their electrostatic forces affect the collective behavior of bulklike hydration water in the nanochannel spaces.…”
Section: Introductionmentioning
confidence: 95%